Impact of Atomic Rearrangement and Single Atom Stabilization on MoSe2@NiCo2Se4 Heterostructure Catalyst for Efficient Overall Water Splitting - Majumdar, Abhisek; Dutta, Pronoy; Sikdar, Anirban; Lee, Heehyeon; Ghosh, Debasis; Jha, Sambhu Nath; Tripathi, Shilpa; Oh, Youngtak; Maiti, Uday Narayan (Wiley - V C H Verlag GmbbH & Co, 2022)
High overpotentials required to cross the energy barriers of both hydrogen and oxygen evolution reactions (HER and OER) limit the overall efficiency of hydrogen production by electrolysis of water. The rational design of heterostructures and anchoring single-atom catalysts (SAC) are the two successful strategies to lower these overpotentials, but realization of such advanced nanostructures with adequate electronic control is challenging. Here, the heterostructure of edge-oriented molybdenum selenide (MoSe2) and nickel-cobalt-selenide (NiCo2Se4) realized through selenization of mixed metal oxide/hydroxide is presented. The as-developed sheet-on-sheet heterostructure shows excellent HER performance, requiring an overpotential of 89 mV to get a current density 10 mA cm(-2) and a Tafel slope of 65 mV dec(-1). Further, resultant MoSe2@NiCo2Se4 is photochemically decorated with single-atom iridium, which on electrochemical surface reconstruction displays outstanding OER activity, requiring only 200 and 313 mV overpotentials for 10 and 500 mA cm(-2) current densities, respectively. A full cell electrolyzer comprising of MoSe2@NiCo2Se4 as cathode and its SAC-Ir decorated counterpart as anode requires only 1.51 V to attain 10 mA cm(-2) current density. Density functional theory calculation reveals the importance of rational heterostructure design and synergistic electronic coupling of single atom iridium in HER and OER processes, respectively.